The principle of customs compliance in customs turnover (Discourse of Law and Administration, 2026)
The aim of the article is to analyze the basic principle of customs law – the customs compliance principle in customs turnover, which is the basic principle of law with which all other principles of customs law must comply. It is not a new principle of law, because its fundamental essence is compliance with customs law provisions, i.e. obligations that legal norms impose on specific persons (addressees).